Assessing the impact of Grant managers on the success of grant applications - Vidal, S.; Laureano, R.; Trindade, M. (Perspectives: Policy and Practice in Higher Education, 2015)
Grant Managers contribute to the mission of research-intensive institutions by helping them to obtain competitive funding. However, their effectiveness in helping institutions and individuals secure funding is poorly studied. In this study, we provide an assessment of the contribution of Grant Managers in attracting competitive funding for research. We compare success rates of funding applications having benefited from specialised input into the grant proposal’s content prior to submission (advanced support) with those having received less support. We collected information from two Grant Offices of Portuguese biomedical research institutions from 2008 to 2011 and focused on the European Commission Marie Curie grants. The results show improved success rates for funding applications which have received advanced support, suggesting that Grant Managers providing specialised support are essential for supporting the research activity. This study fosters the debate on Grant Management assessment and may contribute to a wider recognition of the profession.